Correlation of oxidative stress‐related indicators with milk composition and metabolites in early lactating dairy cows. Issue 6 (29th August 2021) - Zheng, Sen; Qin, Guixin; Zhen, Yuguo; Zhang, Xuefeng; Chen, Xue; Dong, Jianan; Li, Chunlai; Aschalew, Natnael Demelash; Wang, Tao; Sun, Zhe
Abstract: Background: In highly intensive dairy farms, cows often suffer from metabolic disorders that cause severe oxidative stress. Objectives: This study aimed to observe correlations and associations of oxidative stress‐related indicators with milk compositions and metabolites. Methods: Twenty‐two multiparous Holstein dairy cows in early lactation were randomly selected from a commercial dairy farm. The morning milk was collected for composition and metabolites analysis. Blood was sampled via the tail vein to analyze oxidative stress‐related indicators (reactive oxygen species, ROS; catalase, CAT; superoxide dismutase, SOD; glutathione peroxidase, GPX; malondialdehyde, MDA) and metabolites. Results: Results showed that ROS were positively correlated with CAT, GPX, SOD, and MDA. However, the levels of CAT, GPX, and SOD were negatively related to milk fat ( P  <  0.05). Nineteen serum and 7 milk metabolites were selected from detectable metabolites according to their correlations with ROS, CAT, GPX, and SOD ( P  <  0.05). Metabolic pathway analysis and the Kyoto Encyclopedia of Genes and Genomes (KEGG) database revealed that these metabolites are primarily involved in the metabolic pathways of carbohydrates and amino acids. Conclusions: This study gave us a better understanding on oxidative stress that ROS not only increased oxidative damage (MDA) in dairy cows, but also altered some metabolites involved in amino acid and carbohydrate metabolism. Abstract : In highly intensive dairy farms, cows often suffer from metabolic disorders that cause severe oxidative stress. The correlations of oxidative stress‐related indicators with milk composition and metabolites (serum and milk) in multiparous Holstein dairy cows in early lactation were investigated in this study. Results indicated that ROS not only increased oxidative damage in dairy cows but also altered some metabolites involved in amino acid and carbohydrate metabolism.